Peluang dan Tantangan Sektor E-Commerce dalam Meningkatkan Perekonomian di Era Transformasi Digital (Jurnal Simki Economic, 2024)
Digital transformation is carried out through government policies by encouraging people to make optimal use of technology. With digital transformation, customers can easily buy goods online. The digital economy is an economy based on advances in information and communication technology that has no boundaries of distance or place. The economic and social digitalization of society is influenced by e-commerce and social media. So the economic system has changed from a conventional system to a more modern system. The aim of this research is to determine the opportunities and challenges of the e-commerce sector in improving the economy in the era of digital transformation. This research uses a qualitative approach, and data collection is carried out through literature review. Literature studies are obtained from several sources such as journals, essays and books. The research results show that e-commerce opportunities in improving the economy in the digital transformation era are through wider market access, reduced operational costs, product and service innovation. Meanwhile, the challenges of e-commerce in improving the economy include infrastructure and internet access, security and consumer protection, as well as the supply and delivery of goods.